Association between parity and lumbar spine degenerative disorders in young women - Cevik, Serdar; Yilmaz, Hakan; Kaplan, Atilla; Yetkinel, Selcuk; Evran, Sevket; Calis, Fatih; Akkaya, Enes; Katar, Salim; BAYGÜL, ARZU; Hanimoglu, Hakan (My University, 2020)
Introduction: Estrogen helps to maintain the health of collagen-containing tissues including the intervertebral disc. Estrogen deficiency after menopause negatively affects the quality of vertebral end plates and induces development of degenerative disc disease (DDD). However, there is no study examining the relationship between parity and spinal degeneration in young women. The aim of this study was to define the relationship between parity and development of vertebral endplate signal changes and DDD in young premenopausal women. Materials and methods: This case-control case study included 224 patients aged 20-40 years with a history of low back pain for at least 3 months. Pfirrmann-s grade, Modic changes (MCs), and Schmorl-s nodes (SNs) were graded based on magnetic resonance images. Patients- parity, demographics, body mass index, physical activity level, and disability scores were assessed using a questionnaire. Results: The prevalence of abnormal total Pfirrmann-s score (>10) and MCs was higher in primiparous patients than multiparous and grand-multiparous; however, it was not statistically significant. The presence of SN was statistically significantly associated with low parity. According to multivariate logistic regression analysis, it was found that the number of births increases by 1 unit, the abnormality in Pfirrmann-s score decreases by 1.36 times. Conclusions: This cross-sectional study shows that parity is associated with DDD and vertebral end plate changes. SNs were significantly associated with parity. Modic changes and DDD were less common in grand multipara and multipara young women than in primipara women. These results indicate that low parity may possibly be associated with the development of spinal degeneration.